Anisotropic Quantum Transport through a Single Spin Channel in the Magnetic Semiconductor EuTiO3. Issue 24 (8th May 2020) - Maruhashi, Kazuki; Takahashi, Kei S.; Bahramy, Mohammad Saeed; Shimizu, Sunao; Kurihara, Ryosuke; Miyake, Atsushi; Tokunaga, Masashi; Tokura, Yoshinori; Kawasaki, Masashi
Abstract: Magnetic semiconductors are a vital component in the understanding of quantum transport phenomena. To explore such delicate, yet fundamentally important, effects, it is crucial to maintain a high carrier mobility in the presence of magnetic moments. In practice, however, magnetization often diminishes the carrier mobility. Here, it is shown that EuTiO3 is a rare example of a magnetic semiconductor that can be desirably grown using the molecular beam epitaxy to possess a high carrier mobility exceeding 3000 cm 2 V −1 s −1 at 2 K, while intrinsically hosting a large magnetization value, 7 μB per formula unit. This is demonstrated by measuring the Shubnikov–de Haas (SdH) oscillations in the ferromagnetic state of EuTiO3 films with various carrier densities. Using first‐principles calculations, it is shown that the observed SdH oscillations originate genuinely from Ti 3 d ‐ t 2g states which are fully spin‐polarized due to their energetical proximity to the in‐gap Eu 4 f bands. Such an exchange coupling is further shown to have a profound effect on the effective mass and fermiology of the Ti 3 d ‐ t 2g electrons, manifested by a directional anisotropy in the SdH oscillations. These findings suggest that EuTiO3 film is an ideal magnetic semiconductor, offering a fertile field to explore quantum phenomena suitable for spintronic applications. Abstract : Shubnikov–de Haas oscillations in the ferromagnetic state of EuTiO3 are realized. It is shown that the oscillations originate genuinely from Ti 3d‐t2g states, which are fully spin‐polarized due to their energetical proximity to the in‐gap Eu 4f bands. These findings suggest that EuTiO3 film is an ideal magnetic semiconductor, offering a fertile field to explore quantum phenomena.